2018
DOI: 10.1016/j.healun.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 ISHLT/APM/AST/ICCAC/STSW recommendations for the psychosocial evaluation of adult cardiothoracic transplant candidates and candidates for long-term mechanical circulatory support

Abstract: The psychosocial evaluation is well-recognized as an important component of the multifaceted assessment process to determine candidacy for heart transplantation, lung transplantation, and long-term mechanical circulatory support (MCS). However, there is no consensus-based set of recommendations for either the full range of psychosocial domains to be assessed during the evaluation, or the set of processes and procedures to be used to conduct the evaluation, report its findings, and monitor patients' receipt of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
111
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 262 publications
0
111
0
1
Order By: Relevance
“…Many pulmonologists also indicated that poor medication adherence is a barrier to referral which again may reflect this item being considered an absolute contraindication for transplant by the ISHLT [1]. Pretransplant non-adherence increases risk for nonadherence and mortality post-surgically [13], however perfect adherence to a complex CF treatment regimen consumes nearly 2 h each day [14], making adherence challenging for individuals with CF. Studies on CF patient-level barriers to LTx are limited but past nonadherence has been linked to feelings of inferior worthiness for transplant by patients [15].…”
Section: Barriers To Referralmentioning
confidence: 99%
“…Many pulmonologists also indicated that poor medication adherence is a barrier to referral which again may reflect this item being considered an absolute contraindication for transplant by the ISHLT [1]. Pretransplant non-adherence increases risk for nonadherence and mortality post-surgically [13], however perfect adherence to a complex CF treatment regimen consumes nearly 2 h each day [14], making adherence challenging for individuals with CF. Studies on CF patient-level barriers to LTx are limited but past nonadherence has been linked to feelings of inferior worthiness for transplant by patients [15].…”
Section: Barriers To Referralmentioning
confidence: 99%
“…Though inconsistencies in policies are observed across adult transplant programs, there is a general growing consensus across international guidelines and recommendations that active substance abuse is a contraindication for transplantation and that substance use and treatment history should be assessed during transplant evaluations and intervention recommendations should be given . Indeed, the ISHLT’s consensus expert opinion on adult lung transplantation indicates that substance abuse or dependence is an absolute contraindication for transplantation, and evidence of engagement in psychotherapy in addition to blood/urine testing to evince abstinence may be required before transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…The Committee decides whether a candidate is suitable for transplantation, if it is preferable to wait until certain risk factors have been resolved, or if there are medical or psychosocial issues which exclude a candidate from joining the waiting list. Recently, recommendations on the psychosocial evaluation of candidates for heart and lung transplantation as well as indications and contraindications for lung transplantation have been published . In addition, the listing criteria for heart transplantation were updated by the International Society for Heart and Lung Transplantation (ISHLT) .…”
Section: Introductionmentioning
confidence: 99%